PL.40 Access to Obstetric Services in Rural Sub-Saharan Africa: A Hospital Based Survey. (26th April 2013) - Harris, RE; Staffurth, LM; Irvine, L; Hezelgrave, NL; Edmunds, S; Shennan, AH
Abstract : Background: Access to Emergency Obstetric Care (EmOC) is an indicator used to monitor progress towards the achievement of Millennium Development Goals 4 and 5. Lack of access or delay in transportation to hospital is recognised as part of 'The Three Delays Model' and is a major barrier to accessing care for pregnant women living in rural Sub-Saharan Africa. Objective: To determine time taken (minutes) by any mode of transport, to reach an obstetric facility by pregnant women in Zambia, Tanzania and Zimbabwe. Methods: A structured questionnaire in Swahili was used to interview pregnant women from 20–42 weeks gestation who presented to hospital. Results: 750 women were interviewed on the labour ward and antenatal clinics in referral hospitals served by rural antenatal clinics in Zambia (N = 128), Tanzania (N = 246) and Zimbabwe (N = 376). Median gestation was 33.4 weeks (N = 681). 38.8% were primiparous (N = 614). The mean time taken to get from home to obstetric care was 48.3 minutes (IQR = 15–60, median 30). The most common mode of transport was bus (40.6%), followed by foot (30.7%), car (19.3%), bike (9.0%) and other (0.4%) (N = 512). Conclusion: In a sample population of antenatal women who successfully reached the referral site during dry season, average time taken to travel from home to hospital was > 48 minutes. In the wet season and for women in remote rural areas, this is likely to be higher. On foot, during an obstetric emergency, this may represent a significant delay. It is vital that maternal health interventions are designed to address this. Funder: Bill Gates Foundation Grand Challenges Explorations (GCE).